2015
DOI: 10.1155/2015/163591
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechin, EGCG, Suppresses PCB 102-Induced Proliferation in Estrogen-Sensitive Breast Cancer Cells

Abstract: The persistence of polychlorinated biphenyls (PCBs) in the environment is of considerable concern since they accumulate in human breast tissue and may stimulate the growth of estrogen-sensitive tumors. Studies have shown that EGCG from green tea can modify estrogenic activity and thus may act as a cancer chemopreventive agent. In the present study, we evaluated the individual and combined effects of PCB 102 and EGCG on cell proliferation using an estrogen-sensitive breast cancer cell line MCF-7/BOS. PCB 102 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Induction of apoptosis by EGCG is also exerted by the ER-independent actions with the inhibition of aryl hydrocarbon- (AhR-) regulated genes [ 103 106 ]. More recently, Baker and Bauer reported the antiproliferative mechanism of EGCG by blocking the ER β -specific inhibitor PHTPP [ 193 ]. In addition, EGCG is reported to induce the apoptosis in ER-negative MDA-MB-468 [ 104 ] and MDA-MB-231 cells [ 106 , 107 ] and also alters the EGFR activity [ 108 ].…”
Section: Natural Compounds As Therapeuticsmentioning
confidence: 99%
“…Induction of apoptosis by EGCG is also exerted by the ER-independent actions with the inhibition of aryl hydrocarbon- (AhR-) regulated genes [ 103 106 ]. More recently, Baker and Bauer reported the antiproliferative mechanism of EGCG by blocking the ER β -specific inhibitor PHTPP [ 193 ]. In addition, EGCG is reported to induce the apoptosis in ER-negative MDA-MB-468 [ 104 ] and MDA-MB-231 cells [ 106 , 107 ] and also alters the EGFR activity [ 108 ].…”
Section: Natural Compounds As Therapeuticsmentioning
confidence: 99%
“…Therefore, it is urgent to investigate natural compounds like EGCG derived from green tea for the prevention and treatment of cancer and other diseases [ 59 ]. According to previous studies, EGCG is a promising molecule in the prevention and treatment of cancer [ 61 63 ]. Some anticancer properties of EGCG are attributed to its free radical scavenging properties, avoiding the damage of the cell structures induced by the free radicals [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings demonstrated that EGCG has anti-proliferative effects 21,22 . Additionally, green tea also has an affinity for the ovaries and protective effects for the ovaries 10,11 .…”
Section: Discussionmentioning
confidence: 95%